The Implementation of Multicultural Counseling through P5 PPRA at Al Murabby Integrated Boarding School - Rumaisha Aqra, Naila; Suherman AS, Uman; Yusi Riksa Yustiana (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
In this study, discusses the implementation of multicultural counseling through Projek Penguatan Profil Pelajar Pancasila and Profil Pelajar Rahmatan Lil Alamin (P5 PPRA) implemented at the Al Murabby Integrated Islamic Boarding School MAN 1 Kota Bandung. This research uses a qualitative method with a descriptive approach that aims to qualitatively examine the implementation pattern of multicultural counseling at MAN 1 Kota Bandung. In Profil Pelajar, several dimensions and values show that Profil Pelajar does not only focus on cognitive abilities but also attitudes and behaviors following who we are as Indonesians and citizens of the world: (1) believing, fearing God, and having a noble character; (2) global diversity; (3) cooperation; (4) independent; (5) critical reasoning, and (6) creative. Values of religious moderation include; civilization, exemplary, citizenship and nationality, taking the middle way, balancing, straight and firm, equality, deliberation, tolerance, dynamic, and innovation. Keywords: multicultural counseling, profil pelajar pancasila, boarding school